Strategi Pemasaran Produk Industri Rumah Tangga Melalui Penerapan Digital Marketing Di Rt.06 Rw.03 Kelurahan Padang Jati Kota Bengkulu - Tito Irwanto; Tri Seira Febrisa; Yudi Irawan Abi; Iswidana Utama Putra; Anzori Anzori (Universitas Dehasen Bengkulu, 2022)
One of the efforts to improve home industry products and expand the market, especially micro businesses in RT.06 RW.03, Padang Jati Village, Bengkulu City, carried out socialization and guidance to these business actors by utilizing social media as a product marketing tool. With the understanding of business actors about digital, the selling power of products can increase by way of sales that are responsive to consumer needs. The methods of field work carried out by students when doing community service are as follows: (1). Students who do service will visit home industry business owners (2). With an agreement on time and place for the socialization and development of digital marketing which was carried out in RT.06 RW.03 Kelurahan Padang Jati, Bengkulu City, which has 13 household units and is located in the nearest location. (3). Then socialization and training on creating social media accounts were held according to the needs of these business actors